The Skin Photophores of Chauliodus sloani Bloch & Schneider, 1801 (Pisces: Stomiidae): A Morphological, Ultrastructural and Immunohistochemical Study - Mauro Cavallaro; Lidia Pansera; Kamel Mhalhel; Francesco Abbate; Maria Levanti; Maria Cristina Guerrera; Giuseppe Montalbano; Marilena Briglia; Marialuisa Aragona; Rosaria Laurà (Animals, 2025)
This work provides a contribution to the understanding of the structure of the photophores in the mesopelagic fish Chauliodus sloani (family Stomiidae), which occasionally are stranded along the coasts of the Strait of Messina (Central Mediterranean Sea). The analysis was carried out through the study of the structure and ultrastructure of the ventral photophores, and it also includes an immunohistochemical investigation that offers valuable insights into the function of these organs. Studies on photophores help clarify many aspects of the ecology of this species, which represents an important functional link in the marine food web.